Integrating Conversational AI Tools to Enhance Pronunciation, Listening Skills, and Learner Autonomy in Second Language Education - Donny Adiatamana Ginting; Shahzadi Hina (Global Education : International Journal of Educational Sciences and Languages, 2025)
This study investigates the integration of conversational AI tools to enhance pronunciation, listening comprehension, and learner autonomy in second language education. An experimental design was implemented, involving pre-tests, post-tests, questionnaires, and interviews to evaluate learners’ progress after engaging in AI-driven conversation practice. The results indicate significant improvements in pronunciation and listening comprehension, with learners reporting higher confidence, motivation, and independence in managing their own learning. The discussion interprets these outcomes through the lens of second language acquisition theory, emphasizing AI’s role as an accessible conversational partner and its contribution to learner autonomy and lifelong learning. A comparison with previous studies reveals that this research not only confirms the linguistic benefits of AI-assisted learning but also highlights its transformative potential in fostering self-directed learning. The study concludes that conversational AI can serve as an effective complement to traditional instruction, offering both linguistic and motivational advantages for learners in the digital age.